The cooperative dynamics of Brazilian Oil and Gas Innovations Systems A Research Proposal - Gama, Carlos Alexandre Ferreira; Vivacqua, Adriana S (Anais do Simpósio Brasileiro de Sistemas Colaborativos (SBSC), 2019)
Brazilian legislation for the oil and gas sector stipulates a mandatory R&D investment for Oil and Gas Companies. This so-called Petroleum Law led to the establishment of an Innovation System between Universities, Government and Industry (UGI) in which relations between industry researchers and university professors are the heart of this system. From this perspective, modeling the social dynamics of researchers and professors could be considered a relevant contribution to understand the complex dynamic of this Innovation System. This article presents a research proposal to analyze and simulate the social dynamics of cooperation between researchers and professors through the Complex Adaptive Systems lens, in order to understand and measure the possible effects of the investment policy adopted by Brazilian government .